Imagology and iconotextual dialogues : Portuguese culture in Tabucchi's microfiction - Maria João Simões (Études romanes de Brno, 2025)
Narrators who build fictionalised interpretations of different environments and figures of Portuguese culture are presented in the works by Antonio Tabucchi Mulher de Porto Pim, Viagens e outras viagens and Racconti com figure. Based on both imagology theorisation and cosmopolitanism, various aspects of Tabucchi's fictionalisation of the images and figures he uses will be considered. Tabucchi's point of view is characterized by overlapping simultaneous belongings, already visible in his lusophilia, however, his miscegenized point of view only acquires this property because his curiosity of the other makes him a citizen of the world. Tabucchi's peculiar points of view become evident when he recreates and interprets visions of Portuguese painters and writers. An analysis will be made of the resources chosen by the author to transmit to the reader the imagetic crossroads that he felt, the purpose being to distinguish among several variations and aspects used by the author.